Isolation and identification of some Bacterial Species from Common carp (Cyprinus carpio Linnaeus, 1758) in Taqtaq District in Erbil Province, Kurdistan Region, Iraq. - Hussein H. Mala; Shamall M. A. Abdullah (Zanco Journal of Pure and Applied Sciences, 2022)
A number of 220 common carp Cyprinus carpio Linnaeus 1758, were collected from two ponds (98 from pond A and 122 from pond B) in Taqtaq District, northeast from Erbil Province, Kurdistan Region, Iraq. During September 2021 to April 2022. The fishes were examined for bacteria that infect them. In this research revealed the fortune of thirteen species of bacteria. The identification of the isolates was carried out depending on the morphology of the colony, specific media, and identification using VITEK II compact system (Biomerieux- USA). Recording of eight species of bacteria (Streptpcoccus equi zooepidemicus, Methylobacterium spp, Rhizobium radiobacter, Burkholderia cepacia, B. multivorance, B. stabilis, B. vietnamiensis and Sphingobacterium thalpophilum) are considered the first record in Iraq, and recording of five species of bacteria (Staphylococcus lentus, Streptococcus thoraltensis, Klebsiella oxytoca, Pseudomonas aeruginosa and Serratia fonticola) are the fisrt record in Kurdistan Region.